Comparison of surgical and endovascular approaches in the management of multiple intracranial aneurysms. (August 2016) - Dong, Qing-Lin; Gao, Bu-Lang; Cheng, Zhong-Rong; He, Yan-Yan; Zhang, Xue-Jing; Fan, Qiong-Ying; Li, Cong-Hui; Yang, Song-Tao; Xiang, Cheng
Abstract: Objective: To investigate the outcomes and safety of endovascular compared with surgical clipping for multiple intracranial aneurysms. Material and methods: 98 patients with 260 multiple intracranial aneurysms were treated with endovascular, surgical clipping, combined treatment, and observation. Data were retrospectively studied following treatment and at follow-up. Results: In the endovascular group, 44 aneurysms were treated with coils only and 29 aneurysms were treated with stent deployment. The complete occlusion rate was 65%, and the total complication rate was 12% with no permanent deficit. After angiographic follow-up for 1–90 (mean 62) months, the total recurrence rate was 18.3%. In the clipping group, 65 aneurysms were clipped. The complete occlusion rate was 90.8%, and the complication rate was 10.9% with 1 permanent deficit. After follow-up for 11–71 (mean 49) months, the angiographic recurrence rate was 1.5%. In the combination group, 20 aneurysms were treated endovascularly. The complete occlusion rate was 78.9%, and the complication rate was 15.8% with no permanent deficit. Twenty-eight aneurysms were treated surgically with the complete occlusion rate of 89.3%, the complication rate of 20% and 3 permanent deficits. After follow-up for 1–93 (mean 58) months, the angiographic recurrence rate was 33.3% for embolization and 3.6% for clipping. Seventy-four aneurysms for observation had 2.7% regrowth rate within 1–3 years. Conclusion: Endovascular embolization has an accepted complication rate but no neurological deficits compared with surgical clipping and may be a better approach for multiple intracranial aneurysms than surgical clipping. Highlights: Endovascular group: total complication rate 12%, no permanent deficit. Surgical clipping group: total complication rate 10.9%, 1 permanent deficit. Combination group: complication rate of 15.8%, no permanent deficit. Endovascular is a better approach for multiple aneurysms than surgical clipping.